Digital Financial Literacy and Trust in Digital Payment Systems in Shaping Public Decisions to Use Digital Wallets for Daily Transactions - Fania Nabila Lakadjo; Imelda Dian Rahmawati (Politeknik Siber Cerdika Internasional, 2026)
Background: As the digital economy grows rapidly, the use of digital payment solutions, notably digital wallets, has become more common in everyday financial activities. However, the level of digital financial knowledge and trust in digital payment systems significantly impacts individuals' choices to consistently engage with digital wallets. Objective: This investigation explores the extent to which proficiency in digital finance, along with trust in digital payment systems, affects users' willingness to rely on digital wallets for regular spending activities. Methods: The research follows a quantitative approach, collecting responses from 120 community residents via a questionnaire and processing the data using a multiple linear regression model. Results: Digital financial literacy and trust in digital payment systems significantly increase the likelihood of choosing a digital wallet for transactions, both individually and in combination (p = 0.000). Trust emerges as the dominant predictor (β = 0.717), while digital financial literacy (β = 0.336) reinforces rational decision-making in digital spending contexts. The regression model explains 60.1% of the variance in digital wallet usage decisions (R² = 0.601), indicating strong model fit. Conclusion: This study confirms that digital financial literacy and trust in digital payment systems are the two dominant determinants of digital wallet adoption for daily transactions in the general Indonesian public. Future research should expand the variable set to include perceived ease of use, social influence, and hedonic motivation and apply structural equation modeling (SEM) to test mediation and moderation paths.